Effects of the different frequencies of whole-body vibration during the recovery phase after exhaustive exercise - Cheng, C.-F.; Hsu, W.-C.; Lee, C.-L.; Chung, P.-K. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: This study was to investigate the effects of vibration exercise on the oxygen consumption (VO2) and heart rate variability (HRV) during the recovery phase after exhaustive exercise. METHODS: Twenty male college students volunteered as subjects to participate in the study. The subjects were randomly crossover assigned to perform three 10 min vibration exercises, namely non-vibration (CON, 0 Hz, 0 mm), low-frequency (LFT, 20 Hz, 0.4 mm) and high-frequency (HFT, 36 Hz, 0.4 mm) treatments immediately after an incremental exhaustive cycling exercise in separated days. The beat-to-beat HRV, blood lactate concentration and VO2 were measured during the 1-hour recovery phase. The time- and frequency-domain indices of HRV were analyzed to confirm the effects of vibration exercises on the cardiac autonomic modulation. RESULTS: There were no significant differences on the VO2, HRV and blood lactate concentrations at 30th minute (post-30 min) or 60th minute (post-60 min) during the recovery phase among the three treatments. There were also no significant differences on the excess post-exercise oxygen consumption (EPOC) during the recovery phase among the treatments. However, the VO2 at post-30 min in CON and LFT were significantly higher than the baseline values, whereas the VO2 in HFT returned to resting condition at the post-30 min. CONCLUSIONS: The results indicate that both low and high frequency vibration exercises could not improve the physiological recovery after exhaustive cycling exercise. However, the high frequency vibration exercise probably has a potential to facilitate the VO2 to return to the resting level during the recovery phase.